When learning together goes wrong: Negative peer effects in online learning - Shohei Yamamoto; Shuma Iwatani (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This research examined the impacts of peer perseverance on learning outcomes and investigated how this influence varies with the partners' skill levels, either higher or similar to the subjects, across two experiments resembling online learning platforms. Study 1 recruited active English learners, while Study 2 involved subjects who had not engaged in English studies for more than six months. The results of both experiments revealed negative rather than positive peer effects. The subjects ceased studying earlier and displayed lower performance when learning with less perseverant peers, compared to when studying alone. This pattern was observed when paired with similarly skilled peers in Study 1 and with higher-skilled peers in Study 2. Further analysis indicated that the negative peer effects predominantly originated from subjects with lower levels of motivation. Additionally, it was shown that social proximity could foster positive effects when peers possess similar skills and higher perseverance levels.
Keywords: 330; peer effects; perseverance; performance; online learning